2021
DOI: 10.33448/rsd-v10i4.13743
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition, antioxidant activity and anticancer potential of Syzygium cumini (L.) and Syzygium malaccense (L.) fruits

Abstract: Intending to highlight new fruits with nutraceutical potential, the present work reports the nutritional and antioxidant content of Syzygium cumini (L.) Skeels (S. cumini) and Syzygium malaccense (L.) Merr. & LM Perry (S. malaccense), and evaluates the anticancer potential against CP-H460 (lung carcinoma line) and its functionality over HEK-293 (healthy embryonic kidney line), two human cells. For this, the physical-chemical characterization of the lyophilized fruits was carried out, and the content of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…In our other study (Gibbert et al, 2021) we had identified an expressive content of total phenolic compounds in the edible fraction of RJ (202.30 GAE 100g -1 ) and now we confirm that most of this content is found in the peel (269 mg GAE Research, Society and Development, v. 11, n. 2, e33111225578, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i2.25578 10 100g -1 ) of this fruit. That can be attributed to the accumulation of phenolic compounds in the fruit epidermis, acting as a protection against ultraviolet radiation as well as a defense mechanism to certain pathogens and predators (Denardin et al, 2015).…”
Section: Phenolic Compoundsmentioning
confidence: 79%
See 3 more Smart Citations
“…In our other study (Gibbert et al, 2021) we had identified an expressive content of total phenolic compounds in the edible fraction of RJ (202.30 GAE 100g -1 ) and now we confirm that most of this content is found in the peel (269 mg GAE Research, Society and Development, v. 11, n. 2, e33111225578, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i2.25578 10 100g -1 ) of this fruit. That can be attributed to the accumulation of phenolic compounds in the fruit epidermis, acting as a protection against ultraviolet radiation as well as a defense mechanism to certain pathogens and predators (Denardin et al, 2015).…”
Section: Phenolic Compoundsmentioning
confidence: 79%
“…The physicochemical characterization of the edible fraction (pulp and peel) of RJ had previously been reported by Gibbert et al (2021), but in this study, the fruit fractions were separated and characterized individually. Still, the results are similar, (Table 1), and both pulp and peel have an expressive percentage of total soluble solids and high amounts of carbohydrates.…”
Section: Physicochemical Characterizationmentioning
confidence: 96%
See 2 more Smart Citations
“…These results may be explained by the fact that many active components present in the crude extract of ethanol compete. Lung cancer cell viability was found to be considerably decreased by an extract of Syzygium cumini at the highest dose (2 mg/mL) [ 81 ]. This type of cancer is now thought to be the most frequent because of its large prevalence (millions of new cases annually) [ 81 ].…”
Section: Resultsmentioning
confidence: 99%